OCEAN:ICE Annual Project Meeting 2024 Opening Presentation ... - Meijers, Andrew; Mottram, Ruth (Zenodo, 2024)
This presentation was given during the opening session of the OCEAN:ICE Annual Project Meeting on September 23, 2024. Ruth Mottram and Andrew Meijers opened the meeting, presenting the overall progress made in the project since the last annual meeting in 2023. The OCEAN:ICE Annual Project Meeting was held in conjunction with the International Association for the Physical Sciences of the Oceans (IAPSO) joint event, which took place at the Danish Meteorological Institute from September 23 to 25, 2024. The joint event included OCEAN:ICE’s Annual Project Meeting (September 23–24) and a Joint OCEAN:ICE, IAPSO, JCIOI, and SOOS Workshop, ‘Reconciling Cross-Platform Observations of Ice-Shelf Melt (RECOIL),’ on September 25. ...